The utility of SARS‐CoV‐2‐specific serology in COVID‐19 diagnosis. (11th November 2021) - Hasan, Tasnim; Lim, H. Ling; Case, Jennifer; Hueston, Linda; Bag, Shopna; Dwyer, Dominic E.; O'Sullivan, Matthew V.N.
Abstract: Introduction : In May 2020, The Communicable Diseases Network of Australia (CDNA) case definition introduced serological criteria to support the diagnosis of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). We present findings that support the utility of SARS‐CoV‐2‐specific serology for public health investigations. Methods : From 24 January to 31 July 2020, the following information was collected from individuals with positive SARS‐CoV‐2‐specific immunofluorescence antibody tests: history of contact with COVID‐19 cases; recent travel; symptoms consistent with COVID‐19; and SARS‐CoV‐2 nucleic acid testing (NAT) results. Individuals were classified as confirmed or probable by CDNA criteria or additionally as possible (SARS‐CoV‐2‐specific IgG positive with compatible symptoms or epidemiologic risk) or indeterminate (SARS‐CoV‐2‐specific IgA/IgM positive only) cases. Results : A total of 10, 595 individuals were tested in the six‐month period. Of these, 9.8% (1, 037) individuals had positive SARS‐CoV‐2‐specific serology of which 566 (53.6%) were NAT‐confirmed COVID‐19 cases and 286 (27.6%) were part of a cruise ship outbreak sero‐survey. The remaining 185 individuals (NAT negative) were individually classified as serologically confirmed (4, 0.4%), probable (72, 6.9%) possible (66, 6.4%) and indeterminate (38, 3.7%) cases. Maternal antibody transfer was inferred in one infant and four were unclassified. Conclusion : SARS‐CoV‐2‐specific serology is a key diagnostic tool for retrospective identification of COVID‐19 infection. Implications for public health : SARS‐CoV‐2 specific serology can enhance the ability to find cases, link missing cases in clusters of infection and identify the epidemiological extent of SARS‐CoV‐2 outbreaks. A combination of epidemiological criteria, clinical criteria and a quantitative serological test can be used as an adjunct to classify SARS‐CoV‐2 cases. Our study confirms the low level of community transmission in NSW during the first year of the COVID‐19 pandemic